PERILAKU ANOMALI PASAR ATAS AKRUAL KONFORMITAS AKUNTANSI-PAJAK DALAM KONTEKS MODERNISASI SISTEM PERPAJAKAN DI INDONESIA - Kartiko, Sigit Wahyu; Rossieta, Hilda; Wardhani, Ratna (UI Scholars Hub, 2015)
This study aims to analyze the impact of modernization of taxation system and amendment of income tax law on the components of the book-tax conformity accruals, whether there are any differences in the earnings persistence of book-tax conformity accruals (which have higher tax conformity) and book-only accruals (which have lower tax conformity). This study also demonstrates whether the market anomalies occur on those accruals component in the context of taxation in Indonesia. By using 1.729 observations over the years of 2002-2014, this study shows that strategy in book-tax conformity accruals is generally income increasing, while strategy in book-only accruals is income decreasing. The company’s policy on accrual components has different characteristics before and after the implementation of this phase. Governance improvement of taxation authority can increase corporate book-tax conformity accruals. However, when corporate is facing changes in tax laws such as simplification and lower tax rate, they decrease book-tax conformity accruals. Therefore, discretionary book-tax conformity accruals are mispriced by market.